EFFECT OF THE COOLING WITH AIR AND WATER VAPOR ON MILLING PERFORMANCES - Mahmat, Aybars; Tosun, Nihat; Agar, Salih (World Scientific Publ Co Pte Ltd, 2023)
This study aims to investigate experimentally and analytically the effects of different machining parameters such as cooling methods and cutting tool materials on surface roughness and chip thickness ratio for milling of AA7075-T6 aluminum alloy. The carbide and high-speed steel (HSS) end mills were used as cutting tools and the conventional, vapor, and compressed air were used as cooling methods in the experiments. The experiment conditions for compressed air at the cutting zone were 6 bar pressure and 30m/s speed flow rate. A mixture of boron oil and water (1/20 mixture ratio) was used as cutting fluid in conventional cooling. The study was carried out using three levels of feed rates (20, 40, 80mm/min), rotational speeds (780, 1330, 2440rpm), and a constant 2mm deep cut. As a result of the experiments, the surface roughness values increased with the increasing levels of feed rate. Besides surface roughness values decreased with increasing levels of the rotational speed. In addition, a better surface quality was obtained in milling processes by using carbide cutting tools compared to HSS tools. It was concluded that the most important parameter affecting the surface roughness and chip thickness ratio is feed rate and the rotational speed, respectively. Better surface roughness and chip thickness ratio were obtained from the vapor processing than the conventional and compressed air.
Keywords: Milling; surface roughness; chip thickness ratio; aluminium alloy